PENGARUH BUDAYA, PERSEPSI, DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN OBAT HERBAL - Marwati, Marwati; Amidi, Amidi (Jurnal Ilmu Manajemen, 2018)
Along with the high cost of obtaining medical drugs, people find the option touse herbal (non-medical) drugs. However, community acceptance of bothtypes of treatment does not seem to be the same. This research wasconducted to determine the influence of culture, perceptions, and confidencein the purchase decision of herbal medicines.In this study associative design was used by developing three variables(culture, perception, and trust) that were related to the decision to buy herbalmedicines. The sample was determined to be 208 people taken by clustersampling. The data used is primary data with questionnaire data collectionmethod. The data is then analyzed with multiple linear regressiontechniques.The results of the study prove that there are significant effects bothsimultaneously and partially, culture, perception, and trust in the decision topurchase herbal medicines.